A validation study to analyze the reliability of center of pressure data in static posturography in dogs - Aghapour, Masoud; Affenzeller, Nadja; Lutonsky, Christiane; Peham, Christian; Tichy, Alexander; Bockstahler, Barbara (Frontiers in Veterinary Science, 2024)
Center of pressure (COP) parameters are frequently assessed to analyze movement disorders in humans and animals. Methodological discrepancies are a major concern when evaluating conflicting study results. This study aimed to assess the inter-observer reliability and test-retest reliability of body COP parameters including mediolateral and craniocaudal sway, total length, average speed and support surface in healthy dogs during quiet standing on a pressure plate. Additionally, it sought to determine the minimum number of trials and the shortest duration necessary for accurate COP assessment. Twelve clinically healthy dogs underwent 3 repeated trials, which were analyzed by 3 independent observers to evaluate inter-observer reliability. Test-retest reliability was assessed across the 3 trials per dog, each lasting 20 seconds (s). Selected 20s measurements were analyzed in six different ways: 1 × 20s, 1 × 15s, 2 × 10s, 4 × 5s, 10 × 2s, and 20 × 1s. Results demonstrated excellent inter-observer reliability (ICC ≥ 0.93) for all COP parameters. However, only 5s, 10s, and 15s measurements achieved the reliability threshold (ICC ≥ 0.60) for all evaluated parameters. The shortest repeatable durations were obtained from either two 5s measurements or a single 10s measurement. Most importantly, statistically significant differences were observed between the different measurement durations, which underlines the need to standardize measurement times in COP analysis. The results of this study aid scientists in implementing standardized methods, thereby easing comparisons across studies and enhancing the reliability and validity of research findings in veterinary medicine.